Autophagy-dependent secretion: mechanism, factors secreted, and disease implications. Issue 10 (3rd October 2019) - New, Jacob; Thomas, Sufi Mary
ABSTRACT: Although best understood as a degradative pathway, recent evidence demonstrates pronounced involvement of the macroautophagic/autophagic molecular machinery in cellular secretion. With either overexpression or inhibition of autophagy mediators, dramatic alterations in the cellular secretory profile occur. This affects secretion of a plethora of factors ranging from cytokines, to granule contents, and even viral particles. Encompassing a wide range of secreted factors, autophagy-dependent secretion is implicated in diseases ranging from cancer to neurodegeneration. With a growing body of evidence shedding light onto the molecular mediators, this review delineates the molecular machinery involved in selective targeting of the autophagosome for either degradation or secretion. In addition, we summarize the current understanding of factors and cargo secreted through this unconventional route, and describe the implications of this pathway in both health and disease. Abbreviations: BECN1, beclin 1; CAF, cancer associated fibroblast; CUPS, compartment for unconventional protein secretion; CXCL, C-X-C motif chemokine ligand; ER, endoplasmic reticulum; FGF2, fibroblast growth factor 2; HMGB1, high mobility group box 1; IDE, insulin degrading enzyme; IL, Interleukin; MAP1LC3/LC3, microtubule associated protein 1 light chain 3; MAPS, misfolding associated protein secretion; MEF, mouse embryonic fibroblast; MTORC1, MTOR complex I; PtdIns, phosphatidyl inositol; SEC22B, SEC22 homolog B, vesicle trafficking protein (gene/pseudogene); SFV, Semliki forest virus; SNCA, synuclein alpha; SQSTM1, sequestosome 1; STX, Syntaxin; TASCC, TOR-associated spatial coupling compartment; TGFB, transforming growth factor beta; TRIM16, tripartite motif containing 16; UPS, unconventional protein secretion; VWF, von Willebrand factor